Association between serum 25-hydroxyvitamin d and myeloperoxidase: A cross-sectional study of a general population in China - Zhou, Junteng; Li, Ruicen; Bao, Ting; Jiang, Wei; Huang, Yan (Frontiers in Nutrition, 2022)
Background Several studies have found a strong association between cardiovascular diseases and myeloperoxidase (MPO) as a marker of oxidative stress. Although the anti-inflammatory effects of vitamin D in adults have been validated, evidence about the relationship between MPO and 25(OH)D is lacking. This study aimed to investigate the relationship between MPO and 25(OH)D in the general Chinese population. Methods From November 2018 to August 2019, a total of 6414 subjects were enrolled in a tertiary referral hospital in China, which included 3,122 women and 3,292 men. The dependent and independent variables were MPO and 25(OH)D, respectively. The confounders included age, sex, body mass index, waist-hip ratio, smoking status, alcohol drinking status, calcium, and parathyroid hormone concentration. Results In the fully adjusted model, we found that MPO decreased by 0.12 (95% CI −0.16, −0.08), ng/mL for each unit (1 nmol/L) increase in 25(OH)D. When 25(OH) D was divided into quartiles, compared with Q1 (< 41.4 nmol/L), the adjusted beta coefficients (β) of MPO in Q2–Q4 were −2.29 (95% CI, −4.31 to −0.27), −4.76 (95% CI, −6.83 to −2.69), and −6.07 (95% CI, −8.23 to −3.92), respectively (P for the trend < 0.0001). When 25(OH) D was divided according to clinical severity, compared with the severely deficient (< 30 nmol/L) s≥ 30, < 50 nmol/L) and sufficient groups (≥ 50 nmol/L) were −2.59 (95% CI, −5.87 to 0.69) and −5.87 (95% CI, −9.17 to −2.57), respectively (P for the trend < 0.0001). Conclusion After adjusting for age, sex, BMI, waist-hip ratio, smoking status, alcohol status, calcium, and PTH, circulating 25(OH)D was negatively associated with MPO.